THE EFFECT OF THEME AND RHEME TECHNIQUE AND ACHIEVEMENT MOTIVATION ON STUDENTSâ WRITING COMPETENCY AT ENGLISH DEPARTMENT OF THE FACULTY OF TEACHER TRAINING AND EDUCATION OF MAHASARASWATI UNIVERSITY DENPASAR - Leza, Pius (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT The aim of this study was to prove the effect of Theme and Rheme Technique and Achievement Motivation on Studentsâ Writing Competency. This study was conducted in the Fifth Semester of English Department of the Faculty of Teacher Training and Education of Mahasaraswati University in Denpasar with the subjects was the Fifth Semester Students of the Academic Year 2011/2012. The population of this study was 11 classes consisted of 300 students who took writing IV course. From all populations, 60 students were used as sample which were divided into two groups, i.e. experimental group and control group and recruited by using Cluster Random Sampling Technique. The experimental group was semester VC (30 students) and were treated by using Theme and Rheme technique and the control group was semester VD (30 students) and were treated by using Conventional technique. The research design was Posttest Only Control Group Design by using 2x2 factorial design. There were three variables in this study, namely: independent, moderator, and dependent variables. The independent variable was Theme and Rheme technique and moderator variable was studentsâ achievement motivation level (high and low), and the dependent variable was studentsâ writing competency in writing paragraph (short story, personal letter, and business letter). The research used two data-collection instruments, i.e. the writing competency test and the scale of achievement motivation in studying English as foreign language. The data were analyzed by using descriptive statistic and inferential statistic i.e. two-way ANOVA and then continued by using Tukey test. The results of the finding were: (1) there was a significant difference in writing competency between the students who are taught by using Theme and Rheme technique and those who are taught by using Conventional technique. The mean score of the students who are taught by using Theme and Rheme technique was higher than the mean score of the students who are taught by using Conventional technique, (2) there was a significant interactional effect of the techniques of teaching writing (Theme and Rheme technique and Conventional technique) and the studentsâ achievement motivation in learning English on the studentsâ writing competency, (3) there was a significant difference in writing competency between the students with high achievement motivation who are taught by using the Theme and Rheme technique and those taught by using the Conventional technique, (4) there was a significant difference in writing achievement between the students with low achievement motivation who are taught by using the Theme and Rheme technique and those taught by using the Conventional technique, (5) there was a significant difference in writing competency between the students with high achievement motivation and those with low achievement motivation taught by using the Theme and Rheme technique, (6) there was a significant difference in writing achievement between the students with high achievement motivation and those with low achievement motivation taught by using the Conventional technique. Â  Keywords: theme and rheme technique, achievement motivation, studentsâ writing competency